ATTRACTING CHILDREN WITH SPECIAL NEEDS TO GENERAL EDUCATION INSTITUTIONS (American Journal of Interdisciplinary Research and Development, 2024)
In this article, it is difficult to solve the main problems of children with special needs and to achieve social integration if the society does not take responsibility for its members. Solving the problem of equal rights in the education of children with disabilities is one of the urgent problems of today, because many children are left out of education for various reasons. An opinion was expressed about the need to consider the organizational, scientific and methodical measures of involvement in inclusive education, that is, to develop activities related to the training and improvement of the qualifications of specialists.